2000
DOI: 10.1021/jp0025835
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Attractive Interactions in Self-Diffusion

Abstract: Recently, an alternative approach to self-diffusion in atomic liquids was proposed by one of us Szamel, G. Chem. Phys. 1999, 110, 3009]. This approach is applicable where the concept of binary collisions breaks down and the self-diffusion coefficient is small. Predictions from this method are in quantitative agreement with molecular dynamics (MD) simulations, over a broad range of densities and temperatures, for an atomic liquid interacting with a repulsive r -12 potential. Here we extend this approach to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…The different values found for the two models in the high-temperature regime reflect the fact that attractive forces already play an important quantitative role in this regime, despite the very little changes observed in static quantities. This effect was reported before in the case of simple liquids [20][21][22]. The role of attractive forces at high temperatures is partially captured by our MCT calculations, since we find theoretically a 25 % change in E ∞ between the two models.…”
Section: B Relaxation Timessupporting
confidence: 85%
“…The different values found for the two models in the high-temperature regime reflect the fact that attractive forces already play an important quantitative role in this regime, despite the very little changes observed in static quantities. This effect was reported before in the case of simple liquids [20][21][22]. The role of attractive forces at high temperatures is partially captured by our MCT calculations, since we find theoretically a 25 % change in E ∞ between the two models.…”
Section: B Relaxation Timessupporting
confidence: 85%
“…For example, in our earlier work on simple glasses, 12,13 we found that the imaginary frequency modes of such glasses were localized in space for very low temperatures, with extended modes only appearing above the glass transition temperature. To quantify the spatial extent of the normalized eigenvectors (e ␣ i , of each INM, where i runs over the N particles in the sample and ␣ labels the modes͒, we utilize a standard measure of localization, namely, the participation ratio, first introduced by Bell and Dean…”
Section: Instantaneous Normal Modesmentioning
confidence: 82%
“…12,13,21,22 The INMs are defined in analogy with the more familiar normal modes. For an N-particle system at a given temperature T one chooses a configuration ͑defined by a 3N-dimensional vector of atomic coordinates, R 0 ) from the trajectory at some time t 0 .…”
Section: Instantaneous Normal Modesmentioning
confidence: 99%
See 2 more Smart Citations